Bandwidth controlled weakly connected MEMS resonators based narrowband filter. Issue 8 (23rd November 2020) - Behzadi, Kobra; Baghelani, Masoud
Abstract : Electrical tuning of bandwidth is critical for microelectromechanical system (MEMS) resonator‐based narrowband filters especially at ultra‐high frequency ranges and beyond. The resonance frequency of MEMS resonators is highly susceptible to fabrication process uncertainties and very small fabrication variations could result in significant shift in their resonance frequency. Although, disk resonators are the most acceptable candidates for implementing of resonators at GHz frequencies, according to their high stiffness, electrical tuning of these resonators and consequently the resulting filters is almost impossible. This study presents a novel tuning method for low velocity through anchor coupled MEMS radial contour mode disk resonators based on the coupling beam's stiffness tuning using the piezoelectric effect. As the results of this method, high bandwidth tuning ratio as 1:1.25 is achieved due to changing the tuning DC voltage from 0 to 20 V. This impressive result for a narrowband filter with 450 kHz of bandwidth is achieved due to changing the stiffness of low stiff coupling beam which is much easier to control in comparison with extremely high stiffness disk resonators. Various simulation results, as well as analytical works, verify the proposed approach.